The Influence of the Culture of Power, Job Satisfaction and Interpersonal Communication on the Morale of Civil Registry Office Employees in Padang City: Pengaruh Budaya Kekuasaan, Kepuasan Kerja dan Komunikasi Interpersonal Terhadap Semangat Kerja Pegawai Kantor Catatan Sipil Kota Padang Pengaruh Budaya Kekuasaan, Kepuasan Kerja dan Komunikasi Interpersonal Terhadap Semangat Kerja Pegawai Kantor Catatan Sipil Kota Padang - Syailendra Eka Saputra (International Journal of Management and Business (IJMB), 2022)
The purpose of this research is to prove and analyze the influence of the culture of power, job satisfaction and interpersonal communication on the work spirit of Padang Civil Registry Office employees. In this study, the sample was 61 respondents who were selected using the census method. The data analysis method used is multiple regression and t-statistical testing. Based on the results of testing hypotheses that have been carried out found that the culture of power does not have a significant effect on the morale of the Civil Registry Office employees while job satisfaction and interpersonal communication individually have a significant effect on the work morale of Padang Civil Registry Office employees.